An exploration of the legal translator's subjectivity: Analysis of explicitation and implicitation of connectives in the English-Chinese translation of TRIPS. Issue Volume 12:(2016)Special Issue (26th July 2018) - Shi, Junjun
Abstract : The empirical research presented in this paper is an attempt to investigate the legal translator's subjectivity through analyzing the English-Chinese translation of the WTO agreement, TRIPS. The translator's subjectivity is located in the framework of cognitive linguistics, which lends operational dimensions to the current study. Through examining one of these dimensions, explicitation and implicitation, this paper aims to reveal how legal translators exert subjectivity.